1995
DOI: 10.1007/bf00004343
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of the pancreatic and intestinal digestive functions in sea bass (Dicentrarchus labrax): effect of weaning with different protein sources

Abstract: The maturation of the digestive functions in sea bass (Dicentrarchus labrax) larvae was evaluated by the enzymatic profile of pancreas and intestine brush border membranes. Sea bass larvae were weaned at day 25 with three simplified diets different by their protein nature: 100% fish meal (FP), 100% casein mixture (CP) and 50% fish meal-50% casein mixture (CFP). The casein mixture contained 35% of hydrolysate. The control group was fed live preys. The specific activity of amylase decreased with age irrespective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
78
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 31 publications
12
78
0
2
Order By: Relevance
“…Amylase activity before the first ingestion of food was similar to other marine fishes as Theragra chalcogramma (Oozeki and Bailey 1995); Sparus aurata (Moyano et al, 1996); Solea senegalensis (Martínez et al, 1999) and Miichthys miiuy (Xiu et al, 2009), followed by an alternative decrease and increase fluctuating activity which indicates an early presence of amylase activity triggered by specific stimulation discarding mechanism of diet, as may correspond to differences in nutritional requirements and the presence of glycogen in the yolk itself, prior to absorption (Zambonino-Infante & Cahu, 1994;Cahu & Zambonino-Infante 1995;Moyano et al, 1996;Zambonino-Infante & Cahu, 2001;Ribeiro et al, 2002;Xiu et al, 2009). Therefore, the amylase activity may be closely related to its ability to digest carbohydrates present in microalgae as food for zooplankton, and other factors, such as nutrients or digestibility (Moyano et al, 1996).…”
Section: Discussionsupporting
confidence: 52%
“…Amylase activity before the first ingestion of food was similar to other marine fishes as Theragra chalcogramma (Oozeki and Bailey 1995); Sparus aurata (Moyano et al, 1996); Solea senegalensis (Martínez et al, 1999) and Miichthys miiuy (Xiu et al, 2009), followed by an alternative decrease and increase fluctuating activity which indicates an early presence of amylase activity triggered by specific stimulation discarding mechanism of diet, as may correspond to differences in nutritional requirements and the presence of glycogen in the yolk itself, prior to absorption (Zambonino-Infante & Cahu, 1994;Cahu & Zambonino-Infante 1995;Moyano et al, 1996;Zambonino-Infante & Cahu, 2001;Ribeiro et al, 2002;Xiu et al, 2009). Therefore, the amylase activity may be closely related to its ability to digest carbohydrates present in microalgae as food for zooplankton, and other factors, such as nutrients or digestibility (Moyano et al, 1996).…”
Section: Discussionsupporting
confidence: 52%
“…And also these researchers pointed out that protein content of larvae fed Artemia nauplii was higher and the growth of larvae fed the MD was reduced. Besides, it is reported that the trypsin activity contribution of Artemia as a maximum 5% of the total assayed activity in 20-day-old sea bass larvae (Cahu and Zambonino Infante, 1995). On the other hand, histological observations supported these findings that before formation of functional stomach exocrine pancreas have a major role both for the larval digestion and also secretion of pancreatic enzymes such as trypsin, chymotrypsin and other alkaline proteases.…”
Section: Resultsmentioning
confidence: 68%
“…Marine fish larvae, including sea bass, undergo major developmental changes in their digestive functions during the first month of life until the acquisition of an adult mode of digestion (Cahu and Zambonino Infante, 1995;Zambonino Infante and Cahu, 2001). Recent studies have more particularly focused on the functional changes in the digestive tract during larval development by studying the onset and the variation of pancreatic and intestinal digestive enzymes and the response of these enzymes to diet concentration and composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably due to undeveloped digestive tract in early stages of larvae or juveniles. On the other hand, some researchers claimed that some specie' digestive enzyme secretion, especially a high protease and amylase activity, were already existed since early stage of development (Cahu and Zambonino, 1995;Moyano et al, 1996) and it has been hypothesized that this is due to inhibition of enzymes by inadequate protein sources (Alarcon et al, 1999). Also, limited intake of amino acids in charged to produce new body proteins may be caused the presence of enzyme inhibitors in artificial feeds (Garcia-Carreno, 1996).…”
Section: Discussionmentioning
confidence: 99%